AKTIVITAS EMPLOYEE RELATIONS DALAM MEMBINA KINERJA KARYAWAN (STUDI PADA PT. PERTAMINA (PERSERO) RU II SUNGAI PAKNING KECAMATAN BUKIT BATU KABUPATEN BENGKALIS) - Rindu Rahmadini; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Employees is one part of the internal public company that is a key element in achieve the goal. Employmenr relationships is influenced by the internal relations between employees with other employees, or other relationship between employees anf the company management effective. One of the efforts made by PT. Petamina (Persero) is fostering employee performance through employee relations activities in order to continue to produce the best and qualified employees.this study aims to determine the forms of activity of employee relations and describe the activities in fostering employee performance in Pertamina (Persero) RU II Sungai Pakning.This study used qualitative research methods with the presentation of descriptive data analysis and supported by organizational culture theory. The Subjects in this study are determined by purposive sampling techniques consist of head of public relations, the head of human resources and the company's employees. The Data collection techniques included interviews, observation and documentation. The Techniques of analysis used models Miles and Huberman interactive data with data validity check used triangulation techniques.The results of this study showed that the activity of employee relations consist of education and training programs, awards programs, special events programs, and employee benefits programs was instrumental to provided guidance on employee performance. employee relations activity that was applied can not be separated from the culture of the organization in the PT. Pertamina (Persero) RU II Sungai Pakning. Each program was applied have purpose and functions in increasing employee performance. Between the four programs were implementation education and training programs and welfare programs into a program that was the most influential and effective in fostering employee performance. The programs implementation will make employees feel valued and care, so as to create a sense of carrying , motivating, and want to achieve the performance as much as possible, and will minimize negative impacts on the management of a company such as feel boring, saturation, which the result in lower loyalty and productivity of the employees to the company. Key word: Employee relations, Activity, corporation culture,